Development of Microstructure and Mechanical Properties of TiAl6V4 Processed by Wire and Arc Additive Manufacturing - Elitzer, Daniel; Jäger, Stefan; Höll, Clara; Baier, Daniel; Varga, Rosa; Zaeh, Michael F.; Göken, Mathias; Höppel, Heinz Werner (Advanced Engineering Materials, 2022)
Wire and arc additive manufacturing (WAAM) has the potential to significantly reduce material waste due to the milling of components made of TiAl6V4 (Ti-64). To keep up with the market development, this resource-efficient technology is becoming increasingly important to achieve climate policy goals. Therefore, this study not only focuses on the influence of different process parameters, such as torch and wire feed speed, but also different gas mixtures on the microstructure and related mechanical properties, as well as on the scalability by investigating single- to multilayer welded structures. The wire feed speed is found to have a major influence on the geometry and mechanical properties. The use of different process gases, i.e., argon (Ar), helium (He), and a mixture of 70% He and 30% Ar neither significantly affect the microstructure nor the mechanical properties. It is also found that a solution heat treatment followed by an annealing step degrades mechanical properties, while an ordinary stress-relief heat treatment leads to improved mechanical properties. It is shown that by adapting WAAM process and heat treatment parameters, mechanical properties of additively produced specimens can be achieved, which are fully comparable to milled components.
CRIS-Team Scopus Importer:2022-09-30
Keywords: additive manufacturing; alpha-beta alloys; heat treatments; mechanical properties; microstructures; Ti-64; WAAM

Investigation into the influence of the interlayer temperature on machinability and microstructure of additively manufactured Ti-6Al-4V - Fuchs, Christina; Elitzer, Daniel; Höppel, Heinz Werner; Göken, Mathias; Zaeh, Michael F. (Production Engineering, 2023)
The capability of wire and arc additive manufacturing (WAAM) to produce large, near-net-shaped parts with inexpensive equipment has led to the process being considered as one of the options to significantly decrease the buy-to-fly ratio in aircraft manufacture. Even so, there are several challenges associated with the process: achieving mechanical properties and microstructure similar to wrought material, as well as the low surface quality of the parts. The low surface quality is usually improved by milling. As with the microstructure, here too the question arises as to whether the process is comparable to milling wrought material. A significant factor influencing the microstructure according to literature is the interlayer temperature during the WAAM process. Therefore, the objective of this research was to study the influence of the interlayer temperature on the machinability and the microstructure of wire and arc additively manufactured Ti-6Al-4V. Consequently, the machinability was first determined for Ti-Al6-V4-parts manufactured with three different interlayer temperatures. Then, the macro- and microstructures were analyzed and, finally, the mechanical properties were determined. Contrary to expectations based on the state of the art, the machinability was not influenced by the interlayer temperature. This aligns with the mechanical properties and the macro- and microstructures, which are only slightly affected by the interlayer temperature.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Interlayer temperature; Microstructure; Milling; WAAM